Analysis of Green Banking Criteria for the Circular Economy of Coastal Waste As A Model for National Economic Recovery - Suning, Suning; Pungut, Pungut; Ratnawati, Rhenny; Rukmana, Siti Nuurlaily (Faculty of Fisheries and Marine Science, Brawijaya University, 2026)
Coastal areas play a strategic role in national development, yet there remains a disparity between their abundant natural resource potential and community well-being. Various environmental issues, such as poor health outcomes, limited access to clean water, and suboptimal waste management, pose obstacles to improving the well-being of coastal communities. Therefore, a sustainable development approach that integrates economic, social, and environmental aspects is needed. This study aims to develop a Green Banking-Based Circular Economy (GBB-CE) model for waste management in Sukolilo Baru Village, Surabaya, as an effort to support the National Economic Recovery (PEN) in coastal areas. The study employed SWOC (Strengths, Weaknesses, Opportunities, and Challenges) analysis to identify strategic factors, as well as content analysis using NVIVO 12 Plus to explore stakeholders’ perspectives on variables supporting the GBB-CE. The results of the SWOC analysis indicate that active community involvement is a key factor in preserving the environment, including through behaviors such as refraining from disposing of waste into the sea or in locations that could potentially pollute the environment. An analysis using NVIVO 12 Plus shows that small and medium-sized enterprises (SMEs) in the capture fisheries sector emphasize optimizing the economic potential of coastal areas, including the utilization of waste, while the Surabaya City Environmental Agency prioritizes waste reduction and environmental conservation.